PENYULUHAN INDIVIDU (KELUARGA) TENTANG TUBERKULOSIS DAN MEROKOK SEBAGAI UPAYA PENCEGAHAN TUBERKULOSISDI DESA KRAJAN KECAMATAN GATAK KABUPATEN SUKOHARJO - Anika Candrasari; Nia Isnaini; Muhammad Setty Kharyza Aji; Nayla Alivia Putri Abimanyu; Aura Zahra Rahma Priyanto; Yogi Aprisila; Annisa Afanin Aulia (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2026)
This study aims to analyze the relationship between smoking behavior and tuberculosis incidence as well as its implications for disease control efforts. The study employed a descriptive approach through a review of scientific information discussing tuberculosis risk factors, the effects of smoking on the respiratory system, and relevant control strategies. The findings indicate that both active and passive smoking increase susceptibility to tuberculosis because cigarette smoke weakens the immune system and disrupts the natural defense mechanisms of the respiratory tract, thereby facilitating infection. Smoking behavior also contributes to a greater risk of morbidity and mortality associated with tuberculosis, making it a significant obstacle to disease elimination efforts. These findings suggest that tuberculosis control cannot be separated from tobacco control measures. Therefore, integrated collaboration is needed through smoking cessation services, the implementation of smoke-free areas, and the creation of smoke-free environments as part of a comprehensive strategy for tuberculosis prevention and control.